2021
DOI: 10.1016/j.ejca.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The BNT162b2 mRNA COVID-19 vaccine in adolescents and young adults with cancer: A monocentric experience

Abstract: Background and Aims COVID-19 infection in pediatric cancer patients is severe or critical in 20% of the patients. It can therefore directly affect pediatric cancer patients and/or their care. We aimed at evaluating the safety and efficacy of BNT162b2 mRNA Covid-19 vaccine in AYA with solid tumor. Methods Retrospective analysis of safety and efficacy of BNT162b2 mRNA Covid-19 vaccine administered to patients, >= 16 years old, under treatment for a solid tumor or within 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 24 publications
2
47
0
Order By: Relevance
“…Our initial search revealed 3092 records, of which 931 were excluded as duplicates. After screening the titles and, if necessary, full texts, eight published studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] with 2852 children or adolescents and 28 ongoing clinical studies targeting to recruit a total of 122,442 participants were included. The study selection process is shown in detail in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial search revealed 3092 records, of which 931 were excluded as duplicates. After screening the titles and, if necessary, full texts, eight published studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] with 2852 children or adolescents and 28 ongoing clinical studies targeting to recruit a total of 122,442 participants were included. The study selection process is shown in detail in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the eight published studies included, two were RCTs [ 19 , 20 ], two were case series [ 21 , 22 ], and four were case reports [ 23 , 24 , 25 , 26 ]. Five studies were conducted in the United States, and one in China, France, and Israel each.…”
Section: Resultsmentioning
confidence: 99%
“…People with cancer are at an increased risk of experiencing unfavorable outcomes resulting from COVID-19 infection, and recently published position papers, editorials, commentary, and reviews have supported the notion that patients with cancer must receive COVID-19 vaccination when possible [ 26 , 27 ]. However, available clinical data on COVID-19 vaccination in cancer patients are fragmentary and poor [ 18 , 19 , 20 , 21 ]. To our knowledge, this paper is one of the larger report of a prospective, single-center cohort study of anti-COVID-19 vaccination among patients with cancer in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Data on anti-COVID-19 vaccination in cancer patients are limited [ 18 , 19 , 20 , 21 ]. Revon-Riviere et al [ 19 ] reported a retrospective analysis of the safety and efficacy of BNT162b2 mRNA COVID-19 vaccines in adolescents and young adult patients with solid tumors with a median age of 17 years. Of the 10 patients tested, nine had positive serology one month after the second injection, and vaccines had a good safety profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation